Analysis of the Influence of Brand Image and Customer Reviews on Purchase Decisions Mediated by Customer Trust in the Shopee Marketplace - Fahrurrazi, Ridho Ahbib; Susila, Ihwan (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research highlights the importance of brand image management and customer reviews in influencing trust and purchasing behavior on the Shopee Marketplace platform. Research findings confirm that effective brand image management and positive customer reviews have a significant impact on customer trust in a product or brand. This emphasizes the importance of building a strong brand image through the right marketing strategies and responding well to customer reviews. Customer trust is identified as a key factor in influencing purchasing decisions, with companies and sellers needing to focus on building and maintaining trust through quality products, good customer service, and positive brand reputation management. In a competitive e-commerce environment, good brand image management and positive customer reviews have become important aspects in attracting customer interest and influencing purchasing decisions. Therefore, a successful marketing strategy must include efforts to build and maintain customer trust through consistency of experience, product quality, and response to customer reviews. Thus, this research highlights the need for companies and sellers on Shopee to manage and respond to customer reviews well to build a positive brand image and increase customer trust in the e-commerce context.